Motor recovery and antidepressant effects of repetitive transcranial magnetic stimulation on Parkinson disease: A PRISMA-compliant meta-analysis. Issue 18 (May 2020) - Li, Shuqian; Jiao, Rui; Zhou, Xiaomei; Chen, Shangjie
Abstract: Background: Clinical symptoms of Parkinson disease (PD) included both motor and nonmotor symptoms. Previous studies indicated inconsistent results for the therapeutic effects of repetitive transcranial magnetic stimulation (rTMS) on motor and depression in PD. The study aimed to assess the therapeutic effect of rTMS with different mode on motor and depression in PD using a meta-analysis. Methods: Articles published before July 2019 were searched based on the following databases (PubMed, Web of Science, Medline, Embase, and Google Scholar). The therapeutic effects were assessed by computing the standard mean difference (SMD) and a 95% confidence interval (CI). Results: The present study indicated that rTMS showed significant therapeutic effects on motor in PD (SMD 2.05, 95% CI 1.57–2.53, I 2  = 93.0%, P  < .001). Both high-frequency (HF)-rTMS and low-frequency rTMS showed therapeutic effects on motor; stimulation over primary motor cortex (M1), supplementary motor area, dorsal lateral prefrontal cortex (DLPFC) or M1+DLPFC showed therapeutic effects; stimulation during "on" and "off" states showed therapeutic effects; the study showed long-term effect of rTMS on motor in PD. In addition, the study indicated that rTMS showed significant therapeutic effects on depression in PD (SMD 0.80, 95% CI 0.31–1.29, I 2  = 89.1%, P  < .001). Stimulation over left DLPFC showed significant therapeutic effects on depression in PD; only HF-rTMS showed therapeutic effects; ages, disease durations, numbers of pulses, and session durations displayed influence on the therapeutic effects of rTMS on depression in PD; the therapeutic effects on depression was long term. However, no significant difference in therapeutic effects on depression were showed between rTMS and oral Fluoxetine (SMD 0.74, 95% CI −0.83 to 2.31, I 2  = 92.5%, P  < .001). Conclusion: The rTMS showed significant therapeutic effects on motor in PD. HF-rTMS showed a significant positive antidepressive effect in PD only over DLPFC. Abstract : Supplemental Digital Content is available in the text